2022
DOI: 10.3390/agronomy12051185
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Grain Sorghum (Sorghum bicolor (L.) Moench) Cultivars under Intensive Fish Farm Effluent Irrigation

Abstract: The growing global water shortage is an increasing challenge for the agricultural sector, which aims to produce sufficient quantity and quality of food and animal feed. In our study, effluent water from an intensive African catfish farm was irrigated on grain sorghum plants in four consecutive years. In our study the effects of the effluent on the N, P, K, Na content of the seeds, on the phenological parameters (plant height, relative chlorophyll content), the green mass, and on the grain yield of three variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Aquaculture wastewater is rich in organic matter and nutrients such as nitrogen (N), phosphorus (P), and potassium (K) which are important for plant growth (Omotade et al 2019 ; Kimera et al 2023 ; Terkula et al 2023 ). In our study, irrigating sorghum with saline aquaculture wastewater did not show significant detrimental effects in the tested agro-morphological parameters (plant height, leaf area, stalk diameter, and SPAD) and hence in agreement with previous studies (Guimarães et al 2019 , 2022 ; Kolozsvári et al 2022 ). This is because sorghum is moderately tolerant to soil and water salinity of up to 5440 and 2700 ppm respectively above which a 16% reduction in yield is expected (Calone et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Aquaculture wastewater is rich in organic matter and nutrients such as nitrogen (N), phosphorus (P), and potassium (K) which are important for plant growth (Omotade et al 2019 ; Kimera et al 2023 ; Terkula et al 2023 ). In our study, irrigating sorghum with saline aquaculture wastewater did not show significant detrimental effects in the tested agro-morphological parameters (plant height, leaf area, stalk diameter, and SPAD) and hence in agreement with previous studies (Guimarães et al 2019 , 2022 ; Kolozsvári et al 2022 ). This is because sorghum is moderately tolerant to soil and water salinity of up to 5440 and 2700 ppm respectively above which a 16% reduction in yield is expected (Calone et al 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Drought is an environmental factor that negatively impacts plant growth and crop production. As a result of climate change, this factor is manifested more and more often, and its duration has been prolonged in recent years [ 20 , 21 ]. The important role in plant growth and development and the tolerance against abiotic stress, including drought, have growth regulatory factors (GRF).…”
Section: Drought Stressmentioning
confidence: 99%
“…The genetic material of the poplar (Populus trichocarpa) contains a group of seven GT43 genes known as PtrGT43A-G. A complementation study revealed that Poplar PtrGT43A/B/E are IRX9 orthologs, and PtrGT43C/D are IRX14 orthologs [24]. Sorghum (Sorghum bicolor) is the most widely grown food crop due effective use of nitrogen, and extraordinary tolerance to poor soil conditions [25], [26], [27]. Sorghum's genome is smaller (730 Mb) than the genomes of lignocellulosic biomass crops like switchgrass and Miscanthus [28].…”
Section: Introductionmentioning
confidence: 99%